EUPHEMISM OF SURAH AL-BAQARAH IN THE HOLY QURAN - Nurhalimah Tamba; Anni Holila Pulungan; Amrin Saragih (LINGUISTIK TERAPAN, 2019)
This study deals with euphemism of surah Al-Baqarah in the Holy Qur’an. It was aimed to describe realization of euphemistic expressions in surah Al-Baqarah. This study was conducted by using descriptive qualitative research. The data analyzed were verses of surah Al-Baqarah which contained euphemism. The source of the data was taken from Tafseer Ibn Kathir Vol 1-10 in the English language with Arabic verses. The researcher is the key instrument of the research. The findings show that there are four the ways of euphemism realized in surah Al-Baqarah, namely direct, indirect, implicit, and explicit. The dominant of ways realized euphemism in surah Al-Baqarah was direct. It means that the most of euphemism to describe truth from Allah is real and Allah delivered messangers directly about the laws of Allah so that they can know the truth.Keyword: Euphemism, Taboo, Surah Al-Baqarah